Teacher leadership in higher education: why not? - Norma Ghamrawi (7643180) (2024)
This phenomenological investigation examined teacher leadership within the context of higher education among novice faculty members with a specialization in educational leadership. These newcomers received informal guidance and support from specific faculty members whom they identified as exemplifying teacher leadership. The core methodology involved in-depth interviews complemented by bridling journal entries, capturing the lived experiences and perceptions of the six participants from six Arab States. Data analysis employed a whole-part-whole approach. Findings suggest three manifestations or themes for teacher leadership, including social enculturation, expertise diffusion, and emotional fitness. The insights gleaned from this study provide a foundation for fostering discourse on teacher leadership development in higher education contexts. Other Information Published in: Cogent Education License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/2331186x.2024.2366679